Study of Ti-modified columbite route and the effect of lithium doping in 0.9PMN-0.1PT ceramics - Cavalheiro, A. A.; Bruno, J. C.; Zaghete, M. A.; Varela, José Arana [UNESP] (Taylor & Francis Ltd, 2006)
The influence of lithium on the structural characteristics of PMN-PT ceramic was studied. The synthesis of PMN-PT powders using this precursor leads to the formation of high amount of perovskite phase. The insertion of Li(+) ions in B-site affects the microstructure because the rise in mass transport changes the mechanical characteristics of sintered ceramic. Higher values of K(m) and T(m) were gotten when lithium is inserted into perovskite phase. Secondary phase was found when lithium content increase beyond 1 mol%, besides the occurrence of transgranular fractures in sintered ceramic. Also, the additive acts increasing the relaxor behavior.
Keywords: PMN-PT; lithium additive; relaxor ceramics